Involvement of the cerebellum in migraine - Wang, Mengya; Tutt, Joseph O.; Dorricott, Nicholas O.; Parker, Krystal L.; Russo, Andrew F.; Sowers, Levi P. (Frontiers in Systems Neuroscience, 2022)
Migraine is a disabling neurological disease characterized by moderate or severe headaches and accompanied by sensory abnormalities, e.g., photophobia, allodynia, and vertigo. It affects approximately 15% of people worldwide. Despite advancements in current migraine therapeutics, mechanisms underlying migraine remain elusive. Within the central nervous system, studies have hinted that the cerebellum may play an important sensory integrative role in migraine. More specifically, the cerebellum has been proposed to modulate pain processing, and imaging studies have revealed cerebellar alterations in migraine patients. This review aims to summarize the clinical and preclinical studies that link the cerebellum to migraine. We will first discuss cerebellar roles in pain modulation, including cerebellar neuronal connections with pain-related brain regions. Next, we will review cerebellar symptoms and cerebellar imaging data in migraine patients. Lastly, we will highlight the possible roles of the neuropeptide calcitonin gene-related peptide (CGRP) in migraine symptoms, including preclinical cerebellar studies in animal models of migraine.